Model for Technology Acceptance: A Study of Student's Attitude towards usage ofWi-fi Technology - Prateek,; Mehta, Versha (Gyan Management Journal, 2013)
Advanced information technology has become an important means of conducting day-to-day business and life-activities. Strong telecommunication infrastructure is imperative to active
Keywords: Technology Acceptance Model; Wireless Infidelity; Industrial Psychology; Diffusion; Adoption of Innovation